Biochemical and ultrastructural changes in Raillietina echinobothrida in vitro exposed to extract of Lysimachia ramosa - Dey, Paulomi (J Parasit Dis, 2018)
Lysimachia ramosa (Primulaceae) is a traditionally used medicinal plant, leaves extract of which is being widely used by the Jaintia tribes of Meghalaya, India for controlling helminthiasis. Preliminary investigation carried out on helminth parasites revealed that the crude extract of the plant causes deformity in the surface topography leading to death of the parasites. Therefore, the present study was conducted to identify the specific fraction of the crude leaf extract of the plant responsible for cestocidal efficacy, through biochemical and ultrastructural studies in Raillietina echinobothrida exposed to crude extract and its different fractions namely hexane, chloroform, ethyl acetate and n-butanol. A dose dependent efficacy, with highest rate of mortality among n-butanol exposed parasites was recorded. The treated parasites exhibited complete erosion of microtriches from the tegument, disintegration of muscle bundles, cellular organelles, plasma membrane, nuclear membrane, nucleolus and vacuolization of mitochondria was also observed. Observations on histochemical distribution of some important tegumental enzymes like adenosine triphosphatase (ATPase), alkaline phosphatase (AlkPase), acid phosphatase (AcPase) and 5′Nucleotidase (5′-Nu) revealed a marked diminished stain intensity in the tegument of R. echinobothrida exposed to the crude extract and n-butanol fraction of the crude extract compared to the control. Highest reduction (77.93%) in the activity of ATPase was observed when the parasites exposed to 6 mg n-butanol fraction/ml of PBS. The results suggest that these enzymes act as target for anthelmintic stress caused by the phytochemicals present in the plant.